A Semantic Analysis of Denotative and Connotative Meanings in the Lyrics of “Who Knows” by Daniel Caesar - Zaskia Azatil Isma; T. Thyrhaya Zein; Nasqya Rizsa Fatharani; Dzakiah Qurrota Aini; Putri Ramadhani; Rakha Athallah Widya Dhana (Universitas Persada Indonesia YAI, 2026)
The purpose of this research is to identify and interpret the literal and implied meanings that existed in the